Etomatematika: Eksplorasi Konsep Transformasi Geometri Pada Batik Banyumasan - Setyaningrum, Agustina; Kusno, Kusno (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Culture and mathematics are two things that are interrelated, but most people do not realize that they have linked mathematics to their habits and culture. Banyumas is an area in Central Java that has many cultures, and one of these cultures is Banyumasan batik. Banyumasan batik is very famous in Banyumas because it is used by local people as traditional clothing and is even worn by employees on certain days. However, the use of Banyumasan batik is limited to clothing and has not been used in learning, even though the learning material could be more interesting. The aim of this research is to reveal mathematical elements, especially geometric transformations in Banyumasan batik. An ethnographic approach was used in this research, and data collection was carried out through observation, in-depth interviews, documents, and ethnographic notes. Data analysis is based on the meaning and translation of the phenomena found, as well as the informants' understanding of these phenomena and their original language, which is combined verbally with the researcher's language after in-depth understanding through group discussions. The research results show that Banyumasan batik contains geometric transformation elements that can be used in mathematics learning. Keywords: Banyumasan Batik, Culture, Geometry Transformation, Math